Influence of an educative software in the improvement of the handling of the perspective by means of the geometric representation of solids and figures, like element of the development of the space thought (Revista de Investigaciones Universidad del Quindío, 2013)
The aim of this study is to investigate the influence of an educational software in geometric perspective achievement by the geometric representation of Solids and figures as the main elements for the development of the spatial thinking. This study was carried out by a pre-test post-test control group experimental design. In this study researchers took a sample of 36 students from San Jose school, Armenia, Quindío, Colombia in the 2011 school year. Students were distributed into two different groups, experimental group (n=16) and control group (n=16), chosen randomly. Measurements were done by a Pre-test Post-test instrument with 26 reactives. The test has a spearmena-Brown reliability index of 72 %. By means of a student’s t test at the 5% significance level, it was determined that there’s no significant differences between the two groups after the pretest. Using the student’s t test at the 10% significance level, it was determined that there’s significant differences between the group after the post-test. The same test at the 10% significance level show significative differences between pretest and posttest of the experimental group. Finally The same test at the 0.5% significance level show significative differences between pretest and post-test of the control group.
Keywords: educational Software; special thought; management perspective; geometric representation